(3QSGdI aj GdMLQ GdecQes - (3eLghds
(3ChdgG (B:s
(3Qhj aj HYV GdfSN bGd Gddg JYGdi dehSi Ydjg GdSdGe NP LhgQG aGeJg be CMjjg aYdeg Pdc GdMceI hGROGO jbjfG HGdbjGeI hMjGI GdYGde HYO ehJg hRgO aj GdOfjG hYde CfgG OGQ afGA s
(3BNQgG (B:s
(3eKd YGehO GdaVI GdMLQ Ke JCNP ef GdbYdj eG TFJ JWgQg aj GdYSd GdeQSd hGdbWQGf hGdUGHhJ GdeZQHj jOGQ hjbdH aj cd LRA SHY eDGJ Ke JCNP dcd YTQI bdYj hGMO GcSjQ MGQ Ydi MGQ s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs